2009
DOI: 10.1523/jneurosci.4830-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

TheDrosophilaFragile X Mental Retardation Gene Regulates Sleep Need

Abstract: Sleep need is affected by developmental stage and neuronal plasticity, but the underlying mechanisms remain unclear. The fragile X mental retardation gene Fmr1, whose loss-of-function mutation causes the most common form of inherited mental retardation in humans, is involved in synaptogenesis and synaptic plasticity, and its expression depends on both developmental stage and waking experience. Fmr1 is highly conserved across species and Drosophila mutants carrying dFmr1 loss-of-function or gain-of-function mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 74 publications
6
98
2
Order By: Relevance
“…Fly models of fragile X syndrome (FXS) display aberrant circadian output (Dockendorff et al 2002) and sleep. In particular, flies with a loss-of-function mutation in dFmr1 display high sleep need (Bushey et al 2009), perhaps with a specific abnormality of sleep ontogenetic change. Recent work indicates abnormal sleep in a fly model of neurofibromatosis 1 (NF1) (Bai and Sehgal 2015), and NF1 has previously been implicated in circadian output circuitry .…”
Section: Sleep In Neurodevelopmental Mutantsmentioning
confidence: 99%
“…Fly models of fragile X syndrome (FXS) display aberrant circadian output (Dockendorff et al 2002) and sleep. In particular, flies with a loss-of-function mutation in dFmr1 display high sleep need (Bushey et al 2009), perhaps with a specific abnormality of sleep ontogenetic change. Recent work indicates abnormal sleep in a fly model of neurofibromatosis 1 (NF1) (Bai and Sehgal 2015), and NF1 has previously been implicated in circadian output circuitry .…”
Section: Sleep In Neurodevelopmental Mutantsmentioning
confidence: 99%
“…The MBs, functionally analogous to the mammalian hippocampus, are essential for different types of behavior, such as sleep, associative learning, and memory (Davis 1993;Roman and Davis 2001;Joiner et al 2006). The MBs contain the neuronal population required to regulate normal sleep activity; overexpression of dFmr1 in the MBs reduced the prolonged sleep episodes of mutant flies (Bushey et al 2009). In another recent study, dFmr1 mutants showed a deeper night-like sleep phenotype during the day, which was regulated by two molecules, dFMRP and cAMP (van Alphen et al 2013).…”
Section: Dfmr1 Mutant Flies Have Abnormal Circadian Rhythmsmentioning
confidence: 99%
“…We first examined synapse connectivity in the central brain, based on well-established dfmr1 phenotypes. dfmr1 null mutants exhibit strikingly abnormal circadian rhythm patterns, with a complete loss of rhythmicity in the absence of environmental entrainment (Bushey et al, 2009;Dockendorff et al, 2002;Inoue et al, 2002;Sofola et al, 2008). Although Fmr1 knockout mice show only mild impairments, the Fmr1/Fxr2 double knockout is likewise entirely arrhythmic (Zhang et al, 2008).…”
Section: Only Fmr1 Restores Brain Circuit Synaptic Architecturementioning
confidence: 99%